Large Right Atrial Myxoma- An Uncommon Cardiac Tumor Needs Urgent Surgery - Quashem, MA; Roy, Hriday Ranjan; Kibria, Md Golam; Islam, AEM Masharul; Majumder, AA Shafi; Ahsan, NA Kamrul; Ahmed, NU (Journal of Bangladesh College of Physicians and Surgeons, 2010)
A middle aged man was admitted into National Institute of Cardiovascular Diseases with the complaints of intermittent syncopal attack, dyspnoea, low grade fever and headache. After admission, he was diagnosed as a of case right atrial (RA) myxoma by echocardiography. With all preoperative preparation, he was undergone surgery under general anesthesia with cardiopulmonary bypass (CPB). About 9cm x 7cm myxoma was removed and severe tricuspid regurgitation (TR) was found by regurge test. De Vega annuloplasty of the tricuspid annulus was done. Recovery of the patient was satisfactory with disappearance of all symptoms. DOI: 10.3329/jbcps.v27i1.4245 J Bangladesh Coll Phys Surg 2009; 27: 52-55